2019
DOI: 10.1016/j.aucc.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived control and quality of life among recipients of implantable cardioverter defibrillator

Abstract: Background: Perceived control is strongly associated with health-related quality of life (HRQOL) among patients with chronic conditions, and it is possible to increase perceived control with appropriate intervention. Little is known about the relationship between perceived control and HRQOL in implantable cardioverter defibrillator (ICD) recipients. Objectives: To determine the relationship of perceived control with quality of life (QOL) in ICD recipients and to determine predictors of perceived control in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 84 publications
1
11
0
16
Order By: Relevance
“…In the current study, the associations between factors, such as personality (Type D) and heart failure class, and physical and mental QoL and symptoms of depression and anxiety were greater than associations between type of device (S-ICD vs TV-ICD) and shocks during follow-up and these endpoints. This result is consistent with that of other studies in TV-ICD patients, showing that severity of heart failure, 28 lower perceived control, 29,30 anxiety, 29 depression, 29 and Type D personality 30 is more strongly associated with QoL than, e.g., shocks. One study that examined the relative association between heart failure versus device placement on QoL-comparing patients with an ICD without heart failure, patients with heart failure but no ICD, and patients with heart failure and ICD-found that disease severity was more strongly associated with QoL than having a device.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the associations between factors, such as personality (Type D) and heart failure class, and physical and mental QoL and symptoms of depression and anxiety were greater than associations between type of device (S-ICD vs TV-ICD) and shocks during follow-up and these endpoints. This result is consistent with that of other studies in TV-ICD patients, showing that severity of heart failure, 28 lower perceived control, 29,30 anxiety, 29 depression, 29 and Type D personality 30 is more strongly associated with QoL than, e.g., shocks. One study that examined the relative association between heart failure versus device placement on QoL-comparing patients with an ICD without heart failure, patients with heart failure but no ICD, and patients with heart failure and ICD-found that disease severity was more strongly associated with QoL than having a device.…”
Section: Discussionsupporting
confidence: 93%
“…En las variables sociodemográficas de este estudio se resalta la predominancia del género masculino de la muestra (81,2%), información similar a la de una investigación en paises de América del Norte, Europa y Asia con el 79% (15) . Hallazgos similares se observaron en estudios llevados a cabo en China (8) , Japón (16) , Irán (17) , Israel (18) , México (3) , Brasil (19) , Estados Unidos (20,21) , Australia (21) , España (22,23) , Alemania (24,25) , Países Bajos (26,27) , Dinamarca (28)(29)(30) y Suecia (31)(32)(33) . No obstante, en otras publicaciones, poco más del 60% de los participantes correspondían al género masculino (34)(35)(36) , mientras que en otras eran cerca del 68,4% de población masculina (17) .…”
Section: Discussionunclassified
“…En relación con la edad, la media en este estudio fue de 65 años en un rango de 36-92 años, lo cual corresponde al incremento de la población adulta a la que se le implantan cardiodesfibriladores. Estos datos concuerdan con los resultados de estudios que describieron edades medias entre los 60 a 70 años (8,15,18,(20)(21)(22)(23)(24)(25)(26)(30)(31)(32)(33) con rangos extensos entre 17 a 94 años (8,16,22,23,31,33,35) . Otros estudios en países norteamericanos, europeos y oceánicos también han encontrado edades medias inferiores a los 60 años (3,17,19,(27)(28)(29)35,36) .…”
Section: Discussionunclassified
See 2 more Smart Citations